Analysis of the Implementation of the MSME Tax Incentive Policy During the Covid-19 Pandemic (Case Study at KPP Pratama Jakarta Duren Sawit) - Komariah, Yuni (Indonesian Scientific Publication, 2023)
Tax incentives are policies issued by the Indonesian government in the face of the economic slowdown due to the COVID-19 pandemic. This study aims to analyze the implementation of MSME tax incentive policies during the COVID-19 pandemic at the Primary Tax Office of Duren Sawit, Jakarta with a descriptive qualitative method. The results showed that the use of tax incentives by MSME actors at the Primary Tax Office of Duren Sawit, Jakarta was quite effective. This can be seen from the compliance of officers at the Primary Tax Office of Duren Sawit, Jakarta, who have been very good at disseminating this tax incentive policy to MSME taxpayers. The implementation of routine functions has also been going well and in accordance with the procedures provided by the central government. The desired impact has been felt by taxpayers who have taken advantage of incentives which are certainly very helpful.